THE HEALTH BENEFITS OF NATURAL SKIN UVA PHOTOPROTECTIVE COMPOUNDS FOUND IN BOTANICAL SOURCES - Rojas, John; LondoÃ‘o, Cesar; Ciro, Yhors (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
In recent years, botanicals have gained importance due to their dermal photoprotective effect against the harmful UV radiation. This radiation generates reactive oxygen species which attack proteins, lipids, and nucleic acids among others. This leads to the cellular oxidation, which is reflected as tanning, skin inflammation, erythema, immunosuppression, photoaging and skin cancer. The photoprotective activity of synthetic sunscreens is unsatisfactory due the proved incomplete spectral protection, toxicity, and allergenicity. The phytotherapy treatment with antioxidant compounds with potential UV absorbing capacity could offer a more effective photoprotection since they may impede, reverse or delay the process of formation of DNA adducts. The wide diversity of botanicals with photoprotective activity is attributed to several types of substances with phenolic chromophores. These compounds can be classified as flavonoids, phytoestrogens, carotenoids, xhantophylls, coumarins, proanthocyanidins, anthocyanins, catechins, phenolic acids, triterpenes, alkaloids, etc. The bioactivity of these compounds is not limited to the photoprotective action, but antioxidant, anti-inflammatory, antimutagenic and immunomodulatory properties. The regular intake of these botanicals not only prevents but also delays the deleterious effects of sun radiation onto the skin. Therefore, these botanicals have gained considerable attention and are now included in most vitamin and cosmetic products. This review gives an overview of photoprotective botanicals mainly focused on UVA chromophores that are able to inhibit or reverse the damaging effects of sun radiation. The search criterion was made essentially on UVA photoprotective botanicals and related works published in the last ten years. The literature search included mainly the Google scholar, Science direct, and ISI web of knowledge databases. Keywords: Ultraviolet radiation, Photoprotective botanicals, Antioxidants, Phytotherapy.